2016
DOI: 10.1159/000447972
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Lynch Syndrome Mismatch Repair Genes in Women with Endometrial Cancer

Abstract: Objective: Endometrial cancer is the second most frequent neoplasm in women with Lynch syndrome (LS). We sought to assess whether analyzing women with endometrial cancer would identify families with LS not identified with current clinical criteria. Methods: We included women diagnosed with endometrial cancer younger than 50 years and also older if they had a family cancer history associated with LS. In blood samples obtained, we analyzed mutations in mismatch repair (MMR) genes, as well as protein expression b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 19 publications
2
41
0
2
Order By: Relevance
“…It is interesting to note that B-MSI are, at least in our work, frequently found among LS cases and showed preferentially MSH2 and/or MSH6 negativity, in line with those reports describing an absent or mild MSI phenotype when MSH6 gene is involved 17 20. Moreover, this study, one of the few papers addressing MSI test interpretation in ovarian cancers,5 underlined that neoplasms arising in this anatomic site are frequently represented among borderline cases.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is interesting to note that B-MSI are, at least in our work, frequently found among LS cases and showed preferentially MSH2 and/or MSH6 negativity, in line with those reports describing an absent or mild MSI phenotype when MSH6 gene is involved 17 20. Moreover, this study, one of the few papers addressing MSI test interpretation in ovarian cancers,5 underlined that neoplasms arising in this anatomic site are frequently represented among borderline cases.…”
Section: Discussionsupporting
confidence: 90%
“…A little number of reports deal with technical evaluation of MSI testing in GCs,5 17 18 and it is well known that MSI testing in GCs is more tricky than in gastrointestinal cancers 3. However, the high relevance of the detection of MSI GC is supported by the high incidence of MSI tumours among sporadic GC (30%), by the earlier onset of these tumours in female patients with LS, by a favourable clinical outcome19 and by the close relationship between MSI and efficacy of immune checkpoint inhibition 1…”
Section: Discussionmentioning
confidence: 99%
“…In developing a cost‐effective screening strategy, one must consider both the proper patient populations to include and exclude, as well as the optimal testing technology. Studies have repeatedly shown that the existing Amsterdam and Bethesda criteria fail to identify a substantial number of LS patients . Although these criteria generally select for patients under the age of 50, a recent study of 1002 patients with EC by Goodfellow et al determined that 24% of patients with MMR germline mutations are older than 60 years old.…”
Section: Testing For Lynch Syndromementioning
confidence: 99%
“…A separate study analyzed blood samples from patients with EC for pathogenic MMR mutations via sequencing and compared them with tumor tissue‐based MSI and IHC analysis. Among those women with MMR mutations, only 41.66% of samples were positive via MSI and 76.92% positive via IHC, further underscoring the need to test EC patients using a combination of techniques.…”
Section: Testing For Lynch Syndromementioning
confidence: 99%
See 1 more Smart Citation